A system for signals manipulation on the automotive ethernet - Korotetskyi, Oleksandr; Oleksandr Korotetskyi (České vysoké učení technické v Praze, 2024)
Vzhledem k tomu, že automobilový průmysl prochází rychlou transformací směrem k propojeným elektrickým vozidlům a technologiím autonomního řízení, stává se nezbytnou potřebou pokročilá a slibná komunikační řešení jako je Automotive Ethernet. Tato studie se zabývá vztahem mezi automatizací řízení, elektronickou architekturou vozidel a automobilovým sítěním, s důrazem na význam Automotive Ethernetu. Podstatně zkoumá proveditelnost manipulace se signály v síti Automotive Ethernet pro potenciální usnadnění testování vozidel, přičemž řeší zahrnuté výzvy. Nakonec výzkum vede k vývoji a testování softwarového systému navrženého pro sofistikovanou manipulaci se signály, vybaveného schopností obejít bezpečnostní mechanismy, které jsou vyžadovány standardy funkční bezpečnosti.

As the automotive industry undergoes a rapid transformation towards connected electric vehicles and autonomous driving technologies, the need for advanced and promising communication solutions like Automotive Ethernet becomes paramount. This study delves into the relationship between driving automation, vehicle electronic architecture, and automotive networking, emphasizing the significance of Automotive Ethernet. Significantly, it explores the feasibility of signal manipulation within the Automotive Ethernet network for potential facilitation of vehicle testing, addressing the challenges involved. Eventually, the research leads to the development and testing of a software system designed for subtle signal manipulation, equipped to bypass security mechanisms mandated by functional safety standards.
A system for signals manipulation on the automotive ethernet
Keywords: Automotive Ethernet; AUTOSAR; funkční bezpečnost; E/E architektura; automatizace řízení; elektronická řídící jednotka; testování vozidel; software; Automotive Ethernet; AUTOSAR; functional safety; E/E architecture; driving automation; electronic control unit; vehicle testing; software